Cannabidiol Promotes Endothelial Cell Survival by Heme Oxygenase-1-Mediated Autophagy - Sabine Böckmann; Burkhard Hinz (Cells, 2020)
Cannabidiol (CBD), a non-psychoactive cannabinoid, has been reported to mediate antioxidant, anti-inflammatory, and anti-angiogenic effects in endothelial cells. This study investigated the influence of CBD on the expression of heme oxygenase-1 (HO-1) and its functional role in regulating metabolic, autophagic, and apoptotic processes of human umbilical vein endothelial cells (HUVEC). Concentrations up to 10 µM CBD showed a concentration-dependent increase of HO-1 mRNA and protein and an increase of the HO-1-regulating transcription factor nuclear factor erythroid 2-related factor 2 (Nrf2). CBD-induced HO-1 expression was not decreased by antagonists of cannabinoid-activated receptors (CB1, CB2, transient receptor potential vanilloid 1), but by the reactive oxygen species (ROS) scavenger N-acetyl-L-cysteine (NAC). The incubation of HUVEC with 6 µM CBD resulted in increased metabolic activity, while 10 µM CBD caused decreased metabolic activity and an induction of apoptosis, as demonstrated by enhanced caspase-3 cleavage. In addition, CBD triggered a concentration-dependent increase of the autophagy marker LC3A/B-II. Both CBD-induced LC3A/B-II levels and caspase-3 cleavage were reduced by NAC. The inhibition of autophagy by bafilomycin A1 led to apoptosis induction by 6 µM CBD and a further increase of the proapoptotic effect of 10 µM CBD. On the other hand, the inhibition of HO-1 activity with tin protoporphyrin IX (SnPPIX) or knockdown of HO-1 expression by Nrf2 siRNA was associated with a decrease in CBD-mediated autophagy and apoptosis. In summary, our data show for the first time ROS-mediated HO-1 expression in endothelial cells as a mechanism by which CBD mediates protective autophagy, which at higher CBD concentrations, however, can no longer prevent cell death inducing apoptosis.